Study of discoloured iron-gall ink inscriptions – case of the Gradual of Lviv Benedictines from Krzeszow - Aleksandra Surmak (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article describes the study of iron-gall inks in the Gradual of Lviv Benedictine from Krzeszow (Poland). During the conservation and restoration work some untypical color changes of iron-gall inks were observed. This phenomenon contributed to further analysis of the inks in the manuscript and for this purpose some instrumental analysis were conducted, i.a. macro-X-Ray Fluorescence (macro-XRF), optical coherence tomography (OCT) and LIBS. The results provided information about the composition of iron-gall inks in the Gradual from Krzeszów and helped to identify the probable cause of the change in the text layer.